Analytical Technology in Nutrition Analysis - Miranda, Jose M. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Due to increasing global food needs as a result of population growth, the use of new food sources has gained interest in the last decade. However, the inclusion of new foods in our diet, as well as the increased interest of the population in consuming foods with better nutritional properties, has increased the need for adequate food analytical methods. This monographic issue presents innovative methods of chemical analysis of foods, as well as the nutritional and chemical characterization of foods whose consumption is expected to increase worldwide in the coming years.